Towards a National Network of Entomological Collections in Greece - Georgiadis, Christos (ENTOMOLOGIA HELLENICA, 2019)
Although the history of entomological research in Greece spans to more than 2400 years, entomological collecting started about 200 years ago, while established entomological collections were registered about 20 years later. This paper presents the history of these collections giving information on their current status, provides information on the legislation regarding entomological collecting in Greece based on national and international laws and proposes the establishment of a National Network of Entomological Collections.